Educação permanente e a redução da mortalidade infantil em um município do Grande ABC – SP: um estudo de caso - Walendy, Claudia Helena [UNIFESP] (2019)
Combating child mortality is a challenge for societies wishing to improve their social development indicators. This study aimed to analyze how the Municipal Health Secretariat of Mauá, SP, carried out between 2013 and 2016 a successful administrative reform in relation to the reduction of child mortality, listing this issue as a priority, with continuing education actions with emphasis on changes. of work processes with a strong sense of responsibility and intense articulation of management collectives, teams among themselves and among the various services and levels of attention of the health network. This is a case study with documentary analysis of reports and municipal ordinances related to actions to reduce child mortality, interviews with managers and health professionals who worked in the maternal child care network during this period. The results indicate that professionals report this experience as remarkable and enriching, and that even after the completion of this management, some work processes implemented were maintained, but without the same strong network articulation promoted by management. On the other hand, there are also reports of excessive pressure for results and care actions had a strong component of control over the lives of pregnant women by the teams in order to reduce child mortality.